Web-Based Nursing Information System for Credentialing and Training Needs Assessment - Saptarianti, Rahmi (Health Gate, 2024)
The nursing management information system (SIMKEP) is a software package created to facilitate the nursing management process to improve performance and be able to formulate strategic policies including efficiency from within (organisation, management and HR) and must be able to quickly and make appropriate decisions to improve services to the community so that it can become a responsive, innovative, effective, efficient, profitable organisation that is also responsive to developments in science and technology, including information technology. This study aims to determine whether the creation of a website-based nursing management information system application model can improve the nurse credentialing/re-credentialing process and increase the determination of nurse training needs.The method in this research is a mixed studies review or mixed methods review, which combines literature study methods using secondary data from previous research which are published journals, which are by the criteria set by the research, namely the inclusion criteria and systematic exclusion and searches using online databases accompanied by interviews with participants. This article and journal explain that the application model or design of a website-based nursing management information system can improve the credentialing process and determine nurse training needs. The conclusion in writing this Literature Review is that applying a website-based nursing management information system can improve the credentialing process and determine nurse training needs.